Structure, composition and economic potential of molluscs (gastropods and bivalves) in the Lembupurwo Lagoon Beach, Kebumen, Central Java, Indonesia - Yap, Chee Kong; Dwi Setyawan, Ahmad; Rohman, Cahya Maulidta; Kinanti, Asih; Pramudita, Desma Asty; Adil Fadzilah, Fariz Pradana; Ramadhan, Muhammad Fadhil; Faturrahman, Aqra Danial; Aurina, Devi Mayang; Kusuma Dewi, Mini Ambarwati; Ainaya, Fadia Aulianissa; Rachmalia, Fayza; et al. (Generasi Biology Indonesia Foundation, 2024)
The mangrove ecosystem is a productive ecosystem with economic and environmental functions. This research was conducted to determine the value of the ecological index and the economic potential of molluscs (Gastropods and Bivalvia) found in the Lembupurwo Lagoon Beach (part of Wawar River Estuary), Kebumen District, Central Java, Indonesia. Analysis of the data obtained descriptively with the support of tables and pictures. The study results showed that there were 17 species of molluscs consisting of 12 species belonging to the gastropod class and five other species belonging to the bivalves. The families with the most common species are Neritidae=3, Ellobiidae=2, and Littorinidae=2. Whereas in the Bivalvia class, each family was only found one species. The total molluscs found had a density value of 3.95 ind/m2. The Diversity Index (H') of molluscs was 1.48 (moderate), Evenness Index was 0.52 (moderate), Margalef Richness Index was 1.71 (low), and Dominance Index was 0.28 (no species dominated). Then, for the economic potential of the mollusks found, the economic potential is dominated by the food sector. The species that have potential in the food sector include: Faunus ater Linnaeus 1758, Isognomon ephippium Linnaeus 1758, Pilsbryoconcha exilis I.Lea, 1838, Polymesoda expansa Mousson 1849, and Anadara antiquata Linnaeus 1758.